Konstruksi Pembentukan Identitas Kampung Digital Samirono - Endang Supriadi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This paper describes how identity construction carried outby the Kampung DigitalSamirono communities that are part ofthe Kampung Digital program. Because it Samirono villagewhich is known as the hometown of Javanese culture that stillretains the